The Sanctuary of Demeter and Kore: Miscellaneous Finds of Terracotta - Sonia Klinger (Les Carnets de l’ACoSt)
This volume presents the terracotta miscellaneous finds from the Sanctuary of Demeter and Kore at Acrocorinth.